Work-Life Balance and Workload on Employee Work Stress - Ahmad Husnul Khotimah; Rio Nardo (CAKRAWALA : Management Science Journal, 2025)
Job stress is a critical issue in human resource management within the public sector as it directly affects employee performance and organizational effectiveness. This study aims to examine the influence of work life balance and workload on job stress among civil servants at the Directorate of Procurement and Rank, National Civil Service Agency. A quantitative approach with a survey method was employed, where data were collected through a Likert scale questionnaire distributed to the entire population of 57 employees using a total sampling technique. Data analysis involved validity and reliability tests, classical assumption tests, multiple linear regression, t tests, and coefficient of determination with the assistance of SPSS version 30.0. The findings indicate that work life balance has a significant negative effect on job stress, while workload has a significant positive effect on job stress. These results suggest that maintaining a healthy work life balance can reduce employee stress levels, whereas excessive workload increases job pressure. Practically, this study provides insights for government institutions in designing human resource management strategies, particularly by promoting proportional workload distribution and supporting employees’ work life balance, in order to mitigate job stress and enhance organizational effectiveness.